Pengaruh Inovasi Pembelajaran Kontekstual Pkn Terhadap Sikap Nasionalisme Siswa Di Sd Alam Martapura - Arina Wulandari; Wulida Makhtuna; Muhammad Arifin (Jurnal Sultra Elementary School, 2025)
This study aims to analyze the effect of contextual learning innovations in Civics (PKn) on students' nationalistic attitudes at SD Alam Martapura. The background of this study stems from the need for elementary schools to implement a learning approach that is more relevant, meaningful, and close to students' real lives. Contextual learning methods are believed to be able to foster direct learning experiences that encourage students to understand national values ​​more concretely. The study used a quantitative method with a one-group pretest-posttest pre-experimental design. The study sample consisted of 30 fifth-grade students who were selected purposively. Data were collected through a validated and tested nationalistic attitude questionnaire. Data analysis used a t-test to determine significant differences between the results before and after the treatment. The results showed a significant increase in students' nationalistic attitudes after participating in contextual learning in PKn. Students showed improvements in indicators of love for the homeland, discipline, unity, and respect for national symbols. These findings reinforce the idea that contextual learning can be an effective strategy in instilling national values ​​in elementary schools. This research recommends the broader application of contextual learning innovations to other civics subjects and the development of media based on the school environment to enhance meaningful learning.